Frobisher_Bay_Zooplankton_1967-1971_Grainger - Grainger E.H. (Arctic Data Center, 2014)
This dataset represents species composition, distribution and abundance biomass of Zooplankton samples were collected late summer 1967, summer and winter 1970 from Frobisher Bay. Samples were collected with a plankton net of 73 um mesh. Abundance estimates originally described in units of #/m2, and converted to #/m3. Data harvested and rescued from E.H. Grainger. 1971. Biological Oceanographic observations in Frobisher Bay. II. Zooplankton Data, 1967-1970. Fisheries Research Bord of Canada, Technical Report No. 266.